Features of incident colorectal cancer in Lynch syndrome. Issue 8 (1st October 2018) - Argillander, Tanja E; Koornstra, Jan J; van Kouwen, Mariette; Langers, Alexandra MJ; Nagengast, Fokko M; Vecht, Juda; de Vos tot Nederveen Cappel, Wouter H; Dekker, Evelien; van Duijvendijk, Peter; Vasen, Hans FA
Abstract : Background and objective: Despite intensive colonoscopic surveillance, a substantial proportion of Lynch syndrome (LS) patients develop colorectal cancer (CRC). The aim of this study was to characterize incident CRC in LS patients. Methods: All patients diagnosed with incident CRC after start of colonoscopic surveillance were identified in the Dutch LS Registry of 905 patients. A retrospective analysis of patient records was carried out for patient characteristics, survival, CRC characteristics and findings of previous colonoscopy. Results: Seventy‐one patients (7.8%) were diagnosed with incident CRC. Median interval between incident CRC diagnosis and previous colonoscopy was 23.8 (range 6.7–45.6) months. Median tumor diameter was 2.5 cm, and 17% of the tumors were sessile or flat. Most patients (83%) had no lymph node metastases. There was no association between tumor size and colonoscopy interval or lymph node status. Most patients (65%) had no adenomas during previous colonoscopy. Two patients (2.8%) eventually died from metastatic CRC. Conclusion: The high frequency of incident CRC in LS likely results from several factors. Our findings lend support to the hypothesis of fast conversion of adenomas to CRC, as 65% of patients had no report of polyps during previous colonoscopy. High‐quality colonoscopies are essential, especially as tumors and adenomas are difficult to detect because of their frequent non‐polypoid appearance. Early detection due to surveillance as well as the indolent growth of CRC, as demonstrated by the lack of lymph node metastases, contributes to the excellent survival observed.